Redistribution of household income in ireland by taxes and benefits - Nolan, B (Economic & Social Studies, 1981)
Precis: This study uses data published by the CSO based on the 1973 Household Budget Survey to look at the redistribution of income among households by taxes and benefits. The distribution of cash benefits, direct taxes, indirect taxes and non-cash benefits is discussed, with emphasis on the importance of household composition. Decile shares of direct, gross and disposable income are presented and compared with estimates for a number of other countries. Inequality in the distribution of direct income is disaggregated into that within and between households of different compositions. The progressivity of different taxes is examined. Finally, some methodological issues are discussed.
Keywords: Economics; Sociology